2021
DOI: 10.3389/fneur.2021.585189
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Low Oxygen Post Conditioning Improves Stroke-Induced Cognitive Impairment: A Consideration of Amyloid-Beta Loading and Other Mechanisms

Abstract: Cognitive impairment is a common and disruptive outcome for stroke survivors, which is recognized to be notoriously difficult to treat. Previously, we have shown that low oxygen post-conditioning (LOPC) improves motor function and limits secondary neuronal loss in the thalamus after experimental stroke. There is also emerging evidence that LOPC may improve cognitive function post-stroke. In the current study we aimed to explore how exposure to LOPC may improve cognition post-stroke. Experimental stroke was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
3
6
0
Order By: Relevance
“…The IgG labelling suggests that the competence of the BBB in the peri‐infarct and hippocampus was compromised. Similar findings out to 1 month post‐stroke have been previously reported in the peri‐infarct region by us and others using IgG (Zhao et al., 2021) and Evans blue (Weber et al., 2020) extravasation as well as high molecular weight dextran (Yu et al., 2007). BBB disruption has also been observed at different post‐stroke timepoints in regions remote from the infarct, including the hippocampus (Weber et al., 2020) and contralateral hemisphere (Garbuzova‐Davis et al., 2013).…”
Section: Discussionsupporting
confidence: 89%
“…The IgG labelling suggests that the competence of the BBB in the peri‐infarct and hippocampus was compromised. Similar findings out to 1 month post‐stroke have been previously reported in the peri‐infarct region by us and others using IgG (Zhao et al., 2021) and Evans blue (Weber et al., 2020) extravasation as well as high molecular weight dextran (Yu et al., 2007). BBB disruption has also been observed at different post‐stroke timepoints in regions remote from the infarct, including the hippocampus (Weber et al., 2020) and contralateral hemisphere (Garbuzova‐Davis et al., 2013).…”
Section: Discussionsupporting
confidence: 89%
“…The IgG labelling suggests that the competence of the BBB in the peri-infarct and hippocampus was compromised. Similar findings out to 1 month post stroke have been previously reported in the peri-infarct region by us and others using IgG (55) and Evans blue (56) extravasation, as well as high molecular weight dextran (41). BBB disruption has also been observed at different post-stroke timepoints in regions remote from the infarct, including the hippocampus (56) and contralateral hemisphere (57).…”
Section: Discussionsupporting
confidence: 88%
“…57 Further, we demonstrated that the PAL task is sensitive to detect the effects of pharmacological/therapeutic interventions on cognitive recovery in mice after cortical photothrombotic stroke. 29,58 On the other hand, the VDR task includes both visual discrimination and reversal learning, 30,59 with discrimination learning providing a measure of perceptual ability to discriminate between two stimuli, while reversal learning has been used to examine cognitive flexibility. 30 One of the critical variables that we were interested in evaluating in this study is whether the cognitive deficits observed at the subacute phase (7-28 day) would persist or further decline when mice were tested in the chronic phase (56-84 day).…”
Section: Discussionmentioning
confidence: 99%
“…78 For instance, increased Aβ by chronic stress can exacerbate the loss of neurons in sites of SND, 77 whereas reduction of Aβ can alleviate secondary neuronal damage and cognitive function. 10,33,58 It should be noted that Aβ oligomers can also evoke pericyte-mediated constriction of cerebral capillaries, and cause cerebrovascular dysregulation. 79 In addition to our protein analyses, we assessed the spatial distribution of these Aβ oligomers using immunostaining.…”
Section: Discussionmentioning
confidence: 99%